Features of Teaching Cultural Anthropology at American Universities and the Employment of Graduates of Anthropological Faculties in the U.S. in the Late XX-Early XXI Century - Діденко В. (Видавничо-поліграфічний центр "Київський університет", 2013)
The article presents the researchers' points of view for the studying of cultural anthropology in the American universities at the end of XX – beginning of XXI century and also the problem of choosing a career path among the graduates. Scientific methods: comparatively-historical and problematic-chronological. The author comes to conclusions, that there are many benefits to studying anthropology in the US universities. The skills developed through completing a degree in anthropology are useful for living and working in today's world, which increasingly means interacting with people from many different cultural backgrounds and nations. Anthropological training concentrates on three broadly transferable skill areas: understanding human diversity, building research skills for collecting and making sense of information, and communicating effectively.

Проаналізовано особливості викладання культурної антропології в університетах США та з'ясовано тенденції працевлаштування випускників американських антропологічних факультетів в кін. ХХ- на поч. ХХІ ст. Для досягнення поставленої мети, використано порівняльно-історичний та проблемно-хронологічний методи наукового дослідження. Отже, навички отримані під час здобуття ступеня з культурної антропології надзвичайно актуальні для життя і трудової діяльності в сучасному світі, який все більше й більше глобалізується й передбачає комунікацію з людьми з різних культур і народів.
Особливості викладання культурної антропології в американських університетах та працевлаштування випускників антропологічних факультетів в США в кінці ХХ – на початку ХХІ ст.
Keywords: cultural anthropology; regional specialization; theoretical specialization; interdisciplinary discussion; культурна антропологія; регіональна спеціалізація; теоретична спеціалізація; міждисциплінарні дискусії